Field notes contributed by Lee A. Schoenewe, fall 1998 - Schoenewe, Lee A.et al (1998)
Fall report of birds found in northwest Iowa contributed by Lee A. Schoenewe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed